The Influence of Organic Sales Strategy on TikTok Platform Toward Consumer Loyalty in Fashion Products (Case Study of PT Cikal Industries Indonesia): Pengaruh Strategi Penjualan Organik pada Platform TikTok terhadap Loyalitas Konsumen Produk Fashion (Studi Kasus PT Cikal Industries Indonesia) - Ferdian Wahyu Sasetyo; Wiyadi , Wiyadi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The rapid growth of digital technology has transformed consumer behavior, especially in online fashion shopping. This study examines the effect of organic sales strategies on consumer loyalty toward PT Cikal Industries Indonesia on the TikTok platform. Organic strategies utilize TikTok’s algorithm to reach audiences naturally without paid advertising. Using a quantitative survey of 100 TikTok consumers, the study analyzes social media marketing, content marketing, influencers, brand trust, and customer satisfaction as independent variables, with consumer loyalty as the dependent variable. Data were processed using multiple linear regression via SPSS. Results show that social media marketing, content marketing, and brand trust significantly influence consumer loyalty, while influencers and customer satisfaction have positive but less significant individual effects. Collectively, all variables significantly affect consumer loyalty. The findings highlight that organic sales strategies through TikTok effectively strengthen brand-consumer relationships and foster long-term loyalty in the fashion industry.